Design of optimum fault tolerant decoder using five input majority voter based on quantum dot cellular automata. (25th March 2022) - Husain, Shiraz; Gupta, Namit
The semiconductor industry is continuously seeking alternatives to complementary metal oxide semiconductor (CMOS) technology for further shrinking and portability in devices. Quantum-dot cellular automata (QCA) is a good nominee and vibrant research topic in nano-regime from last two decades. Since fabrication of QCA is vulnerable to defects, fault tolerant component and circuit design strategies are necessary to circumvent the effects. As majority voter is most basic element in QCA, the reliability of circuits depends on the accurate working of the majority gates. The paper proposes a new five-input majority voter and 2 × 4 decoder with high fault tolerance against several structural defects. An analytical approach is also used for representation of single cell omission defect. The comparative analysis of five input majority voter and decoder is done with previous designs in literature. The proposed designs exhibit high fault tolerance and works equally good in other performance parameters as well.